Low COVID-19-related practice increases the risk of poor health literacy in international students - Sevinc, Nergiz; Korkut, Burcu (Faculty of Medicine, Universitas Trisakti, 2021)
Background Health literacy (HL) is the ability to access, understand, appraise, and apply health information, making it crucial for navigating coronavirus and COVID-19 information environments. The objective of this study was to determine the health literacy of international students who could not return to their countries after announcement of the coronavirus disease (COVID-19) pandemic and their perspective and behavior about COVID-19.MethodsA cross-sectional study was conducted involving 399 international students. A 73-item questionnaire consisting of health literacy (23 items), knowledge, attitude and practice about Covid-19 (37 items), and sociodemographic characteristics (13 items) was answered by the students. The relationship between the HL score and various variables was determined using univariate and multiple binary logistic regression. Results Of the 399 international students, 322 (80.7%) participated. The HL of the international students was found to be poor (78.0%) and good (22.0%). Participants’ COVID-19-related behaviors: 8.4% of the participants’ knowledge level was good, and 38.5% had high COVID-19 related practice. Multivariate models showed that HL was independently and significantly associated with COVID-19 related practice (OR= 6.27; 95% CI: 2.45 - 15.79; p=0.000). ConclusionThis study revealed that international students’ HL was poor and that low COVID-19 related practice increased the risk of low HL in international students. According to the findings, further efforts should be made to enhance levels of HL and COVID-19-related behavior of international students.